Modeling and Optimization of Carbon Dioxide Methanation via in Situ Hydrogen Generated from Aluminum Foil and Alkaline Water by Box–Behnken Design - Zamani, A. H.; Nor Hakimin, Abdullah (Elsevier Ltd, 2018)
The catalytic activity of carbon dioxide (CO2) methanation by in situ hydrogen generated from aluminum foil (Al) and alkaline water over a novel catalyst (AHZ–CM) was investigated. Response surface method- ology involving Box–Behnken design (RSM-BBD) was implemented for optimization where the reaction temperature was found to be the utmost significant effective factor, followed by H2/CO2 ratio and weight catalyst loading. The optimum condition for CO2 conversion was at 3.29g of weight catalyst loading, H2/CO2 ratio of 4.08 and reaction temperature of 276.7 °C which resulted in 97.5% of CO2 conversion. The result was approximately in agreement with the predicted result found by RSM which achieved 99.9% CO2 conversion. Interestingly, this study proved that the hydrogen gas production from Al and alkaline water can be used in situ reaction and the novel catalyst (AHZ–CM) would be an excellent candidate to be used for CO2 methanation reaction.